2006
DOI: 10.1002/jbm.b.30474
|View full text |Cite
|
Sign up to set email alerts
|

Examination of surface properties and in vitro biological performance of amorphous diamond‐like carbon‐coated polyurethane

Abstract: Despite the emerging use of diamond-like carbon (DLC) as a coating for medical devices, few studies have examined the resistance of DLC coatings onto medical polymers to both microbial adherence and encrustation. In this study, amorphous DLC of a range of refractive indexes (1.7-1.9) and thicknesses (100-600 nm) was deposited onto polyurethane, a model polymer, and the resistance to microbial adherence (Escherichia coli; clinical isolate) and encrustation examined using in vitro models. In comparison to the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…As seen, random incorporation of increasing amount of fluorine atoms to an initial DLC structure or a raw UHMWPE surface resulted in the presence of more oxidized CF X species, and this was correlated to an increase of the WCA. The WCA not only can indicate the hydrophilic/hydrophobic behavior of the surface, but also it seems to be intimately related to the surface roughness and the surface tension 31, 34. Surface roughness could significantly influence bacterial adherence because interstitial spaces or irregularities on the surface can supply extra anchorage sites for bacteria 35.…”
Section: Discussionmentioning
confidence: 99%
“…As seen, random incorporation of increasing amount of fluorine atoms to an initial DLC structure or a raw UHMWPE surface resulted in the presence of more oxidized CF X species, and this was correlated to an increase of the WCA. The WCA not only can indicate the hydrophilic/hydrophobic behavior of the surface, but also it seems to be intimately related to the surface roughness and the surface tension 31, 34. Surface roughness could significantly influence bacterial adherence because interstitial spaces or irregularities on the surface can supply extra anchorage sites for bacteria 35.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies regarding bacterial adhesion on the different carbon films have been published before (Wang et al, 2004, Ishihara et al, 2006, Jones et al, 2006, Katsikogianni et al, 2006, Morrison et al, 2006, Kwok et al, 2007, Zhao et al, 2007, Zhou et al, 2008, Kinnari et al, 2008. These works included mainly DLC or modified-DLC films and concluded that the carbon surface has great biocompatibility properties and good resistance to microbial adhesion.…”
Section: Bacterial Adhesionmentioning
confidence: 99%
“…Furthermore, a sequence of events that leads to the foreign body reaction following implantation of a medical device, prosthesis, or biomaterial is also presented in a review [4]. Therefore, owing to the problems associated with the use of medical devices, there is a clinical need for the development of novel materials [5] and novel coatings including diamond-like carbon (DLC) coatings over existing materials that will offer resistance to infection and encrustation [6][7][8][9], design of biomaterials with antimicrobial surfaces through some new surface modification techniques [10,11], and finally the use of novel approaches to deliver antimicrobial agents for eradicating the biofilm consortia from the medical devices.…”
Section: Introductionmentioning
confidence: 97%